Designing, developing and testing an eDNA sampling payload system with winch capabilities for Unmanned Aerial Vehicles (UAVs) - Christy, Nitin Leonard; Prakasam Prabhakaran, Harsha (My University, 2025)
This master’s thesis focuses on advancing the development of a Drone assisted Environmental DNA (eDNA) testing system, a relatively new approach to enhancing precision and efficiency in biodiversity monitoring. This approach will significantly simplify the sample collection process, reducing the need for manual intervention. The goal of this master’s thesis was to develop concepts and then to prototype it into a robust near-prerelease product. The scope of this thesis involved extensive RD to develop an eDNA sampling payload system with a winch which lowers the sampling equipment 5m below the surface of the water. The emphasis was to develop a water floating payload and to reduce the payload weight to better enable the drone to carry the sampling apparatus more easily and efficiently. This included material selection and structural optimization to obtain a lighter, yet robust design. The addition of functional components with a winch system was important to control the descent and recovery of the water sampling device. An Arduino-based control system was integrated in the design, managing the electronic components housed within the payload. This upgrade aimed to automate the sampling process and provide easier remote access to the payload. This master’s thesis project discusses how the prototype was developed from concept to a complete functional, aesthetic product for field testing with potential for commercial application. The progress made in payload design, and functional components marks a leap towards a more capable and user-friendly eDNA testing approach that can positively impact biodiversity monitoring and environmental studies.